Short and Long-Term Outcomes of Diabetes Mellitus in Patients with Autoimmune Pancreatitis after Steroid Therapy - Miyamoto, Yuji (The Korean Society of Gastroenterology; the Korean Society of Gastrointestinal Endoscopy; the Korean Association for the Study of the Liver; the Korean Society of Neurogastroenterology and Motility; Korean Association for the Study of Intestinal Diseases; Korean College of Helicobacter and Upper Gastrointestinal Research; Korean Pancreatobiliary Association; Korean Society of Gastrointestinal Cancer, 2012)
BACKGROUND/AIMS: Autoimmune pancreatitis (AIP) is frequently associated with diabetes mellitus (DM). This study evaluated the effect of steroid therapy on the course of DM in AIP. METHODS: Glucose tolerance was examined in 69 patients with AIP. DM onset was classified as either a simultaneous onset with AIP or an exacerbation of pre-existing DM. Based on the changes in the HbA1c levels and insulin dose, the responses of DM to steroids were classified as improved, no change, or worsened. RESULTS: Thirty (46%) patients were diagnosed as having DM (simultaneous onset, n=17; pre-existing, n=13). Three months after starting the steroid treatment, the DM improved in 13 (54%) of 24 DM patients. The DM improved in 55%, had no change in 36%, and worsened in 9% of the 11 simultaneous onset DM patients, and it improved in 54%, had no change in 31%, and worsened in 15% of the 13 pre-existing DM patients. At approximately 3 years after starting the steroid treatment, the DM improved in 10 (63%) of 16 patients. The pancreatic exocrine function improved in parallel with the changes in the DM in seven patients. CONCLUSIONS: Because approximately 60% of DM associated with AIP is responsive to steroids in the short- and long-terms, marked DM associated with AIP appears to be an indication for steroid therapy.